Atomistic insights on the pressure-induced multi-layer graphene to diamond-like structure transformation. (30th April 2021) - Geng, Peng; Branicio, Paulo S.
Abstract: Recent results suggest a pressure-induced transformation of bilayer graphene to a diamond-like structure. Intriguingly, the reported transformation is absent or incomplete in multi-layer graphene beyond two layers, implying the suppression of the transformation by an unclear mechanism. In this work, we use reactive molecular dynamics simulations to describe the pressure-induced structural evolution of multi-layer graphene with two to six layers to pressures up to 200 GPa. The results show that bilayer graphene transforms into a diamond-like film, i.e., more than 75% sp 3 hybridized atoms. In contrast, three- to six-layer graphene with AB layer stacking fail to form a diamond-like film up to 200 GPa. Bond formation analysis indicates that the transformation or its suppression is related to the generation of a bond chain structure across layers, connecting sp 3 hybridized atoms. The result suggests that the ABA layer stacking is directly related to the hindering of the chain structure formation and the suppression of the transformation. Surprisingly, the bond-chain-structure transformation mechanism is effective in three-layer graphene with ABC layer stacking, as well as five-layer graphene with ABCAB layer stacking. That suggests that stacking faults are effective catalysts for the high-pressure transformation of multi-layer graphene to diamond. Graphical abstract: Image 1